2015
DOI: 10.31129/lumat.v3i2.1043
|View full text |Cite
|
Sign up to set email alerts
|

Species knowledge in pre-service teacher education: Experiences from an educational activity

Abstract: Experiences shows that the knowledge of species among teacher students has decreased the last twenty years, and recent research from different parts of the world shows the same: The knowledge of species is decreasing. As an introduction to their science teacher education 39 students followed a course over seven weeks, where they learned more about plant and animal species in three different biotopes:forest, mountain and freshwater. The students replied to a questionnaire five weeks after the course. Both the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(7 reference statements)
0
0
0
1
Order By: Relevance
“…However, there is a great lack of knowledge of the nearby fauna, whether in danger of extinction or common. These results are in agreement with other investigations [31,32,37,38]. In this regard, the finding that endangered species are more recognizable than other common native species is certainly significant, as it means that preschool teachers are aware of some of the local environmental issues, perhaps due to the media activity [51,52].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, there is a great lack of knowledge of the nearby fauna, whether in danger of extinction or common. These results are in agreement with other investigations [31,32,37,38]. In this regard, the finding that endangered species are more recognizable than other common native species is certainly significant, as it means that preschool teachers are aware of some of the local environmental issues, perhaps due to the media activity [51,52].…”
Section: Discussionsupporting
confidence: 92%
“…In relation to the interest of the taxonomic level of biodiversity, several studies analyze species knowledge in the educational world. For example, Kvammen (2015) [36], points out that species knowledge among pre-service teachers has decreased over the last 20 years. Lindemann-Matthies et al, (2017) [32], in a study conducted in Germany with pre-service teachers, found that these future teachers are able to identify 23% of plants and 44% of animals from a sample of species inhabiting environments close to the students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En relación con el interés del nivel taxonómico de la biodiversidad son varios los estudios que analizan el conocimiento de las especies en el mundo educativo. Así, por ejemplo, Kvammen (2015), señala que el conocimiento de las especies entre el profesorado en formación ha decrecido en los últimos 20 años. Una investigación de Lindemann-Matthies et al (2017), entre profesores de Primaria en formación de Alemania, determina que menos de una cuarta parte es capaz de identificar plantas y menos de la mitad animales de una muestra de especies de hábitats próximos a los estudiantes.…”
Section: La Importancia Del Estudio De La Diversidad Biológica En Las...unclassified
“…Researchers in different parts of the world focused on Biodiversity awareness and species identification and conducted several studies. Kvammen (2015) reported a decrease in the species awareness level of prospective teachers over the last 20 years (Kvammen, 2015).…”
Section: Introductionmentioning
confidence: 99%